2004
DOI: 10.3390/e6050413
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation Due to Laminar Incompressible Forced Convection Flow Through Parallel-Plates Microchannel

Abstract: The entropy generation due to steady laminar forced convection fluid flow through parallel plates microchannel is investigated numerically. The effect of Knudsen, Reynolds, Prandtl, Eckert numbers and the nondimensional temperature difference on entropy generation within the microchannel is discussed. The fraction of the entropy generation due to heat transfer to the total entropy generation within the microchannel is studied in terms of Bejan number. The entropy generation within the microchannel is found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…Similar to the case of Newtonian fluid (Hung, 2009), the findings of this work show that for non-Newtonian fluid also under certain conditions the viscous dissipation effect on entropy generation in microtubes is significant and should not be neglected. Haddad et al (2004) investigated entropy generation due to steady laminar forced convection fluid flow through parallel plates microchannel. It is found that entropy generation decreases as Knudsen number increases, and increases as Reynolds, Prandtl, Eckert numbers and the non-dimensional temperature difference increase.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the case of Newtonian fluid (Hung, 2009), the findings of this work show that for non-Newtonian fluid also under certain conditions the viscous dissipation effect on entropy generation in microtubes is significant and should not be neglected. Haddad et al (2004) investigated entropy generation due to steady laminar forced convection fluid flow through parallel plates microchannel. It is found that entropy generation decreases as Knudsen number increases, and increases as Reynolds, Prandtl, Eckert numbers and the non-dimensional temperature difference increase.…”
Section: Introductionmentioning
confidence: 99%
“…The Bejan number is a dimensionless number defined as the entropy generation ratio of the thermal irreversibility over the total entropy generation [30,31]. That is:…”
Section: All the Input Data For Calculationmentioning
confidence: 99%
“…In one of such works, Haddad et al [4] studied numerically the entropy generation in fluid flow through parallel plate microchannel. The fluid flow is assumed to be steady laminar.…”
Section: Introductionmentioning
confidence: 99%